A Sub-Threshold Microwave RFID Tag Chip, Compatible With RFID MIMO Reader Technology - Haddadian, Sanaz; Scheytt, J. Christoph; von Bögel, Gerd; Grenter, Thorben (IEEE Journal of Radio Frequency Identification)
We present a fully integrated radio frequency identifications transponder chip operating at 5.8 GHz, which is compatible with the class-1 generation-2 of the Electronic Product Code protocol (EPC-C1 G2). The tag chip including the analog front-end and the digital baseband processor, are designed in the sub-threshold regime (0.5 V) with a total supply current of less than 50 μA. As a power scavenging unit, a single-stage differential-drive rectifier structure is designed and fabricated with standard threshold voltage (SVT) MOS elements in a commercial 65-nm CMOS process, to provide 0.8 V of rectified voltage. Measurements performed on the fabricated single-stage structure show a maximum power conversion efficiency of 69.6% for a 22 kΩ load and a sensitivity of -12.5 dBm, which corresponds to more than 1 m of reading range. The power conversion efficiency at this range is about 64%.

Design of individual simulation games in manufacturing companies for game-based learning - Machon, Fabian; Gabriel, Stefan; Latos, Benedikt; Holtkötter, Christoph; Lütkehoff, Ben; Asmar, Laban; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Impact of 3D Curvature on the Polarization Orientation in Non-Ising Domain Walls - Acevedo-Salas, Ulises; Croes, Boris; Zhang, Yide; Cregut, Olivier; Dorkenoo, Kokou Dodzi; Kirbus, Benjamin; Singh, Ekta; Beccard, Henrik; Rüsing, Michael; Eng, Lukas M.; Hertel, Riccardo; Eliseev, Eugene A.; et al. (Nano Letters)
Ferroelectric domain boundaries are quasi-two-dimensional functional interfaces with high prospects for nanoelectronic applications. Despite their reduced dimensionality, they can exhibit complex non-Ising polarization configurations and unexpected physical properties. Here, the impact of the three-dimensional (3D) curvature on the polarization profile of nominally uncharged 180° domain walls in LiNbO3 is studied using second-harmonic generation microscopy and 3D polarimetry analysis. Correlations between the domain-wall curvature and the variation of its internal polarization unfold in the form of modulations of the Néel-like character, which we attribute to the flexoelectric effect. While the Néel-like character originates mainly from the tilting of the domain wall, the internal polarization adjusts its orientation due to the synergetic upshot of dipolar and monopolar bound charges and their variation with the 3D curvature. Our results show that curved interfaces in solid crystals may offer a rich playground for tailoring nanoscale polar states.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Pseudo-Labeling Machine Learning Algorithm for Predictive Maintenance of Relays - Winkel, Fabian; Wallscheid, Oliver; Scholz, Peter; Böcker, Joachim (IEEE Open Journal of the Industrial Electronics Society)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Control and Systems Engineering

Run-to-Failure Relay Dataset for Predictive Maintenance Research With Machine Learning - Winkel, Fabian; Deuse-Kleinsteuber, Johannes; Böcker, Joachim (IEEE Transactions on Reliability)
Keywords: Electrical and Electronic Engineering; Safety; Risk; Reliability and Quality

K-12 Data Science Education: Outcomes of a National Workshop; International Perspectives; and Next Steps for the Learning Sciences - Wilkerson, Michelle; Ben-Zvi, Dani; Dvir, Michal; Matuk, Camilla; Podworny, Susanne; Stephens, Amy; Zapata-Cardona, Lucia (General Proceedings of the ISLS Annual Meeting: Building Knowledge and Sustaining our Community)

Plant-based dietary patterns and cardiometabolic risk factors in subgroups of individuals with diabetes - Weber, Katharina S.; Schlesinger, Sabrina; Lang, Alexander; Straßburger, Klaus; Maalmi, Haifa; Zaharia, Oana P.; Goletzke, Janina; Buyken, Anette; Trenkamp, Sandra; Wagner, Robert; Lieb, Wolfgang; Roden, Michael; et al. (Diabetologie und Stoffwechsel)

GEProS - Entwicklung und Evaluation einer digitalen Simulation zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden - Grotegut, Lea
Um Schüler*innenmerkmale korrekt zu beurteilen benötigen Lehrkräfte diagnostische Kompetenz. Insbesondere die genaue Einschätzung nicht-kognitiver Merkmale von Schüler*innen fällt Lehrkräften eher schwer. Dazu zählen auch mögliche Anzeichen für Lern- und Verhaltensauffälligkeiten. Maßnahmen zur Förderung diagnostischer Kompetenz fokussieren bisher größtenteils die Diagnostik fachspezifischer, situativer Urteilsgegenstände, wie Fehlkonzepte im Mathematikunterricht. Systematisch evaluierte Fördermaßnahmen, die das Erkennen und Beurteilen von Lern- und Verhaltensauffälligkeiten bei Schüler*innen fokussieren, existieren bisher nicht.Aus diesem Anlass wurde die digitale, problemorientierte Simulation GEProS zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden entwickelt und systematisch in drei längsschnittlichen, (quasi-)experimentellen Kontrollgruppenstudien evaluiert. Die Ergebnisse zeigen, dass die GEProS einen Mehrwert für die Förderung diagnostischer Kompetenz insbesondere im Bereich selbstbestimmter Motivation bieten kann. Ein integriertes Quiz mit Feedback kann mittels testing effect darüber hinaus der Erwerb deklarativ-konzeptionellen Wissens als zentrale Disposition diagnostischer Kompetenz in GEProS unterstützen. Die Ergebnisse tragen durch das entwickelte Integrative Modell diagnostischer Kompetenz zur Theoriebildung sowie zur Forschung und Entwicklung im Bereich der Förderung diagnostischer Kompetenz bei, indem eine Maßnahme zur Förderung diagnostischer Kompetenz für einen fächerübergreifenden, zeitlich stabilen Urteilsgegenstand systematisch evaluiert wurde. Durch die Ableitung und Berücksichtigung wesentlicher Merkmale digitaler Simulationen trägt diese Arbeit außerdem zur theoretischen Fundierung digitaler Simulationen bei.

Frontal theta reveals further information about neural valence‐dependent processing of augmented feedback in extensive motor practice—A secondary analysis - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (European Journal of Neuroscience)
Abstract Supplementing an earlier analysis of event‐related potentials in extensive motor learning (Margraf et al., 2022a, 2022b), frontal theta‐band activity (4–8 Hz) was scrutinized. Thirty‐seven participants learned a sequential arm movement with 192 trials in each of five practice sessions. Feedback, based on a performance adaptive bandwidth, was given after every trial. Electroencephalogram (EEG) was recorded in the first and last practice sessions. The degree of motor automatization was tested under dual‐task conditions in a pre‐test–post‐test design. Quantitative error information was transported in both feedback conditions (positive and negative). Frontal theta activity was discussed as a general signal that cognitive control is needed and, therefore, was expected to be higher after negative feedback. Extensive motor practice promotes automatization, and therefore, decreased frontal theta activity was expected in the later practice. Further, it was expected that frontal theta was predictive for subsequent behavioural adaptations and the amount of motor automatization. As the results show, induced frontal theta power was higher after negative feedback and decreased after five sessions of practice. Moreover, induced theta activity was predictive for error correction and, therefore, an indicator of whether the recruited cognitive resources successfully induced behavioural adaptations. It remains to be solved why these effects, which fit well with the theoretical assumptions, were only revealed by the induced part of frontal theta activity. Further, the amount of theta activity during practice was not predictive for the degree of motor automatization. It seems that there might be a dissociation between attentional resources associated with feedback processing and attentional resources associated with motor control.
Keywords: General Neuroscience

Feedback processing in cognitive and motor tasks: A meta‐analysis on the feedback‐related negativity - Faßbender, Laura; Krause, Daniel; Weigelt, Matthias (Psychophysiology)
Abstract For motor learning, the processing of behavioral outcomes is of high significance. The feedback‐related negativity (FRN) is an event‐related potential, which is often described as a correlate of the reward prediction error in reinforcement learning. The number of studies examining the FRN in motor tasks is increasing. This meta‐analysis summarizes the component in the motor domain and compares it to the cognitive domain. Therefore, a data set of a previous meta‐analysis in the cognitive domain that comprised 47 studies was reanalyzed and compared to additional 25 studies of the motor domain. Further, a moderator analysis for the studies in the motor domain was conducted. The FRN amplitude was higher in the motor domain than in the cognitive domain. This might be related to a higher task complexity and a higher feedback ambiguity of motor tasks. The FRN latency was shorter in the motor domain than in the cognitive domain. Given that sensory information can be used as an external feedback predictor prior to the presentation of the final feedback, reward processing in the motor domain may have been faster and reduced the FRN latency. The moderator variable analysis revealed that the feedback modality influenced the FRN latency, with shorter FRN latencies after bimodal than after visual feedback. Processing of outcome feedback seems to share basic principles in both domains; however, differences exist and should be considered in FRN studies. Future research is motivated to scrutinize the effects of bimodal feedback and other moderators within the motor domain.
Keywords: Experimental and Cognitive Psychology; Neuropsychology and Physiological Psychology; Biological Psychiatry; Cognitive Neuroscience; Developmental Neuroscience; Endocrine and Autonomic Systems; Neurology; Experimental and Cognitive Psychology; Neuropsychology and Physiological Psychology; General Neuroscience

Imagine to automatize: automatization of stimulus–response coupling after action imagery practice in implicit sequence learning - Dahm, Stephan F.; Hyna, Henri; Krause, Daniel (Psychological Research)
Abstract Action imagery practice (AIP) describes the repetitive imagination of an action to improve subsequent action execution. Because AIP and action execution practice (AEP) draw on partly similar motor mechanisms, it was assumed that AIP may lead to motor automatization, which is observable in a reduction of dual-task costs after AEP. To investigate automatization in AIP, we compared dual-task and single-task performance in practice and random sequences in pretests and posttests. All participants practiced serial reactions to visual stimuli in ten single-task practice sessions. An AIP group imagined the reactions. An AEP group and a control practice group executed the reactions. Practice followed a sequential sequence in AIP and AEP but was random in control practice. In dual-task test conditions, tones were counted that appeared in addition to the visual stimuli. RTs decreased from pretest to posttest in both practice and random sequences in all groups indicating general sequence-unspecific learning. Further, RTs decreased to a greater extent in the practice sequence than in the random sequence after AIP and AEP, indicating sequence-specific learning. Dual-task costs—the difference between RTs after tone and no tone events—were reduced independent from the performed sequence in all groups indicating sequence-unspecific automatization. It is concluded that the stimulus–response coupling can be automatized by both, AEP and AIP.
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Application-based learning of signal analysis methods with the help of a graphical open-source software - Hetkämper, Tim; Koch, Kevin; Webersen, Manuel; Claes, Leander (SEFI 51th Annual Conference Proceedings - Engineering Education for Sustainability)

Finite-Set Direct Torque Control via Edge Computing-Assisted Safe Reinforcement Learning for a Permanent Magnet Synchronous Motor - Schenke, Maximilian; Haucke-Korber, Barnabas; Wallscheid, Oliver (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

"Security is not my field, I’m a stats guy": A Qualitative Root Cause Analysis of Barriers to Adversarial Machine Learning Defenses in Industry - Mink, Jaron; Kaur, Harjot; Schmüser, Juliane; Fahl, Sascha; Acar, Yasemin (32nd USENIX Security Symposium, USENIX Security 2023, Anaheim, CA, USA, August 9-11, 2023)

Learning the pronunciation of segmental features of english phonology at german primary schools - Hahn, Charlotte Anna
In der vorliegenden Arbeit wird die Auswirkung expliziter Ausspracheübungen auf die englische Aussprache von Kindern an Grundschulen in NRW untersucht. Das Ziel dieser Arbeit ist es, eine Alternative für den mittel-offenen vorderen Vokal /æ/ und die dentalen Frikative /, ð/ zu bieten. Es wurde eine Interventionsstudie mit 72 Teilnehmenden aus drei verschiedenen Grundschulklassen durchgeführt; zwei vierte Klassen mit verschiedenen Lehrkräften und eine dritte Klasse, die von der Lehrperson einer der vierten Klassen unterrichtet wurde. Jede Klasse wurde in eine Kontroll- und zwei Interventionsgruppen (je eine für den Vokal und die Konsonanten) geteilt. Alle Gruppen wurden einmal zu Beginn und zwei Mal am Ende der Studie getestet. Zwischen den letzten beiden Tests lagen sechs bis acht Wochen, um einen mittelfristigen Effekt zu testen. Die Intervention, die nach der ersten Messung stattfand, wurde auf zwei je ca. drei-minütige Einzelsitzungen aufgeteilt. Während der Intervention übten die Teilnehmenden mit der Autorin die Aussprache des relevanten Phonems. Die Ergebnisse dieser Studie zeigen, dass die Interventionen einen Effekt auf die Aussprache der Teilnehmenden hatten. Wie sich dieser Effekt verhält und entwickelt scheint von der Art des Phonems, dem Alter der Teilnehmenden sowie der bisherigen Ausspracheschulung abzuhängen. Die vorliegenden Ergebnisse liefern Erkenntnisse nicht nur für die Grundschule selbst, sondern auch für die Lehrer*innenausbildung und Lehrplanentwicklung.

The Choice of Ideology and Everyday Decisions - Burs, Carina; Gries, Thomas; Müller, Veronika (Journal of Organizational Psychology)
Individuals strive to make decisions that are consistent with not only their consumer preferences but also their psychological needs. However, they are confronted with complex, ambiguous or even false information. Ideologies and belief systems provide guidance when processing and evaluating information and give a coherent and comprehensible interpretation of reality. The first question is: why is an individual attracted to a particular ideology? Individuals choose ideologies that resonate with their subjective psychological needs and preferences. Second, how do individuals search for ideologies and find out which suit them best? We model an individual’s sequential information search for the best matching ideologies by applying Bayesian learning and utility optimization. Additional information enhances utility by reducing uncertainty. As a search is costly, the process may stop once an individual adopts an ideology even if the information set remains incomplete. Third, once they have chosen a particular ideology, individuals adhere to its rules and norms when making everyday decisions. Consumers not only physically consume, but they also act in accordance with their psychological needs.
Keywords: Economics; Ideology; Decision-making

One size does not fit all: Investigating strategies for differentially-private learning across NLP tasks - Senge, Manuel; Igamberdiev, Timour; Habernal, Ivan (Proceedings of the 2022 Conference on Empirical Methods in Natural Language Processing)

Protein intake and type 2 diabetes mellitus: an umbrella review of systematic reviews for the evidence-based guideline for protein intake of the German Nutrition Society - Schulze, Matthias B.; Haardt, Julia; Amini, Anna M.; Kalotai, Nicole; Lehmann, Andreas; Schmidt, Annemarie; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Kühn, Tilman; Louis, Sandrine; et al. (European Journal of Nutrition)
Abstract Purpose Protein-rich foods show heterogeneous associations with the risk of type 2 diabetes (T2D) and it remains unclear whether habitual protein intake is related to T2D risk. We carried out an umbrella review of systematic reviews (SR) of randomised trials and/or cohort studies on protein intake in relation to risks of T2D. Methods Following a pre-specified protocol (PROSPERO: CRD42018082395), we retrieved SRs on protein intake and T2D risk published between July 1st 2009 and May 22nd 2022, and assessed the methodological quality and outcome-specific certainty of the evidence using a modified version of AMSTAR 2 and NutriGrade, respectively. The overall certainty of evidence was rated according to predefined criteria. Results Eight SRs were identified of which six contained meta-analyses. The majority of SRs on total protein intake had moderate or high methodological quality and moderate outcome-specific certainty of evidence according to NutriGrade, however, the latter was low for the majority of SRs on animal and plant protein. Six of the eight SRs reported risk increases with both total and animal protein. According to one SR, total protein intake in studies was ~ 21 energy percentage (%E) in the highest intake category and 15%E in the lowest intake category. Relative Risks comparing high versus low intake in most recent SRs ranged from 1.09 (two SRs, 95% CIs 1.02–1.15 and 1.06–1.13) to 1.11 (1.05–1.16) for total protein (between 8 and 12 cohort studies included) and from 1.13 (1.08–1.19) to 1.19 (two SRs, 1.11–1.28 and 1.11–1.28) (8–9 cohort studies) for animal protein. However, SRs on RCTs examining major glycaemic traits (HbA 1c , fasting glucose, fasting insulin) do not support a clear biological link with T2D risk. For plant protein, some recent SRs pointed towards risk decreases and non-linear associations, however, the majority did not support an association with T2D risk. Conclusion Higher total protein intake was possibly associated with higher T2D risk, while there is insufficient evidence for a risk increase with higher intakes of animal protein and a risk decrease with plant protein intake. Given that most SRs on plant protein did not indicate an association, there is possibly a lack of an effect.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Protein intake and body weight, fat mass and waist circumference: an umbrella review of systematic reviews for the evidence-based guideline on protein intake of the German Nutrition Society - Ellinger, Sabine; Amini, Anna M.; Haardt, Julia; Lehmann, Andreas; Schmidt, Annemarie; Bischoff-Ferrari, Heike A.; Buyken, Anette; Kroke, Anja; Kühn, Tilman; Louis, Sandrine; Lorkowski, Stefan; Nimptsch, Katharina; et al. (European Journal of Nutrition)
Abstract Purpose This umbrella review aimed to assess whether dietary protein intake with regard to quantitative (higher vs. lower dietary protein intake) and qualitative considerations (total, plant-based or animal-based protein intake) affects body weight (BW), fat mass (FM) and waist circumference (WC). Methods A systematic literature search was conducted in PubMed, Embase and Cochrane Database of Systematic Reviews for systematic reviews (SRs) with and without meta-analyses of prospective studies published between 04 October 2007 and 04 January 2022. Methodological quality and outcome-specific certainty of evidence of the retrieved SRs were assessed by using AMSTAR 2 and NutriGrade, respectively, in order to rate the overall certainty of evidence using predefined criteria. Results Thirty-three SRs were included in this umbrella review; 29 were based on randomised controlled trials, a few included cohort studies. In studies without energy restriction, a high-protein diet did not modulate BW, FM and WC in adults in general (all “possible” evidence); for older adults, overall certainty of evidence was “insufficient” for all parameters. Under hypoenergetic diets, a high-protein diet mostly decreased BW and FM, but evidence was “insufficient” due to low methodological quality. Evidence regarding an influence of the protein type on BW, FM and WC was “insufficient”. Conclusion “Possible” evidence exists that the amount of protein does not affect BW, FM and WC in adults under isoenergetic conditions. Its impact on the reduction in BW and FM under hypoenergetic conditions remains unclear; evidence for an influence of protein type on BW, FM and WC is “insufficient”.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Alignment between timing of ‘highest caloric intake’ and chronotype in relation to body composition during adolescence: the DONALD Study - Jankovic, Nicole; Schmitting, Sarah; Stutz, Bianca; Krüger, Bettina; Buyken, Anette; Alexy, Ute (European Journal of Nutrition)
Abstract Purpose Our aim was to assess alignment in timing of ‘highest caloric intake’ with individual chronotype and its association with body composition in adolescents. Methods We used repeatedly collected data from n = 196 adolescents (age 9–16 years, providing N = 401 yearly questionnaires) of the DONALD open cohort study. Chronotype was assessed by the Munich Chronotype Questionnaire from which midpoint of sleep (MSFsc) was derived. A sex- and age-specific diet-chrono-alignment score (DCAS) was calculated as the difference in hours between the chronotype-specific median timing of highest caloric intake of the studied population and the individual timing of ‘highest caloric intake’ or vice versa. Repeated-measures regression models were applied to study cross-sectional and longitudinal associations between the DCAS and body composition, e.g., Fat Mass Index (FMI) or Fat Free Mass Index (FFMI). Results DCAS ranged from −6:42 h to + 8:01 h and was not associated with body composition. Among adolescents with a later chronotype ( N = 201) a 1 h increase in DCAS (later consumption of ‘highest caloric intake’ in comparison to the median intake of that group), increased FFMI by 1.92 kg/m 2 (95% CI: 0.15, 3.69, p value = 0.04) over a median follow-up of 0.94 year. Conclusion Alignment of energy intake with individual chronotype appears beneficial for FFMI among those with a late chronotype.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Innovative self-learning disturbance compensation for straightening processes - Bathelt, Lukas; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar (Materials Research Proceedings)
Abstract. To increase the sustainability of forming processes such as punch bending, homogenization of the processed semi-finished product is an essential step in the manufacturing process. High-strength wire materials are usually available as strip material before being further processed in a forming process. For storage and transport, the material is coiled onto coils and transported to the customer. During the coiling process, residual stresses and plastic deformation are introduced into the wire. Thus, the final product quality is also influenced by the geometry of the coil. Straightening machines are used in production lines to compensate for these. Once a straightening machine has been set up, the settings for the roll positions are usually not changed. As a result, there is no reaction to material fluctuations, which means that the components to be produced do not meet the dimensional accuracy requirements. This leads to an increase in the rejection rate in manufacturing processes. To reduce the rejection rate, it is necessary to enable dynamic and flexible infeed of the straightening rollers. In this context, an innovative control concept with disturbance compensation was developed for the straightening process. The disturbance compensation uses a disturbance model that predicts the change in bending curvature over the coil radius. With this prediction, the straightening machine can be adjusted specifically. The roller positions are adjusted by a subordinate position control. The additional feedback from measured geometric product properties from the following punching-bending process enables the straightening machine to be adjusted even in the case of unforeseen fluctuations in the material properties. In this way, it is possible to react to any material fluctuations as required. This novel, demand-oriented adjustment of the straightening machine is expected to result in a high increase in the efficiency of the production process and a reduction of the rejection rate.

Learning the Automated Setup of Profile Wrapping Lines for New Products from Few Past Setups - Koppert, Steven; Bause, Maximilian; Henke, Christian; Trächtler, Ansgar (2023 IEEE 21st International Conference on Industrial Informatics (INDIN))

Evidence-based practices in teaching - Rybska, Eliza; Dudziak, Renata; Pollmeier, Pascal (Problemy Wczesnej Edukacji)
This article presents the results of the implementation of the Erasmus Plus project (KA203 financed by the European Union, contract number 2019-1-NL01-KA203-060339) Research in Teacher Education (RiTE). The aim of the project was to promote and facilitate pre-service teachers to create and undertake evidence-based practices in teaching science, technology, engineering, and mathematics (STEM). In the RiTE project, pre-service teachers were encouraged to use evidence from educational and scientific research and to experiment and introduce didactic innovations in teaching and learning processes. Although it has its justification in the tradition of thinking about science, evidence-based practice is not yet consciously applied in school practice. In the article, we present both the theoretical framework for such practices, and the results of qualitative research – an analysis of interviews conducted with students, future teachers, and novice teachers involved in the project. The presented results show changes in the context of an understanding of evidence and what evidence-based practices are in the teaching process and the vision of such teaching presented by the respondents.

Incremental permutation feature importance (iPFI): towards online explanations on data streams - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (Machine Learning)
Abstract Explainable artificial intelligence has mainly focused on static learning scenarios so far. We are interested in dynamic scenarios where data is sampled progressively, and learning is done in an incremental rather than a batch mode. We seek efficient incremental algorithms for computing feature importance (FI). Permutation feature importance (PFI) is a well-established model-agnostic measure to obtain global FI based on feature marginalization of absent features. We propose an efficient, model-agnostic algorithm called iPFI to estimate this measure incrementally and under dynamic modeling conditions including concept drift. We prove theoretical guarantees on the approximation quality in terms of expectation and variance. To validate our theoretical findings and the efficacy of our approaches in incremental scenarios dealing with streaming data rather than traditional batch settings, we conduct multiple experimental studies on benchmark data with and without concept drift.
Keywords: Artificial Intelligence; Software

Role (in-)congruity and the Catch 22 for female executives: how stereotyping contributes to the gender pay gap at top executive level - Diederich, Sarah; Iseke, Anja; Pull, Kerstin; Schneider, Martin (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

Class Expression Learning with Multiple Representations - Ngonga Ngomo, Axel-Cyrille; Demir, Caglar; Kouagou, N'Dah Jean; Heindorf, Stefan; Karalis, Nikoloas; Bigerl, Alexander (Compendium of Neurosymbolic Artificial Intelligence)

Schulkulturbezogene Schultypen im Zeitalter der digitalen Transformation. Eine Typologie unter Berücksichtigung von Hintergrundmerkmalen der zur Schulkultur befragten Lehrkräfte - Caruso, Carina; Drossel, Kerstin; Heldt, Melanie (MedienPädagogik)
In view of technological progress, a digitalisation deficit in German schools as well as the experiences in schools as a result of the Corona pandemic, it becomes apparent that the question of a school culture conducive to learning retains its relevance in the age of digital transformation: On the one hand, it is evident that school culture changes in view of the digital transformation. On the other hand, it contributes to the successful implementation of digital media. Previous research findings in connection with the digital transformation focus on particular competencies of teachers (Meyer, Becker, and Bock 2023; Caruso, Heldt, and Drossel 2022; Vogelsang et al. 2023) and their cooperative behaviour (Drossel and Heldt 2022; Schulze, Drossel, and Eickelmann 2022). These questions whether school culture-related school types can be identified or not and how teachers perceive the school culture have been less considered so far. This article is dedicated to this question and explores if the school culture-related school types differ in terms of the background characteristics of the teachers. Based on a Latent Class Analysis, three school culture-related school types become apparent: strong in innovation and cooperation (Type I: 45.74 %), highly innovative and inhibited cooperation (Type II: 17.95 %), inhibited in terms of innovation and cooperation (Type III: 36.31 %). The types do not differ from each other regarding the background characteristics.

Role (in-)congruity and the Catch 22 for female executives: how stereotyping contributes to the gender pay gap at top executive level - Diederich, Sarah; Iseke, Anja; Pull, Kerstin; Schneider, Martin (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

Reconstruction of 3D Surfels from Neural Radiance Fields - Telaprolu, Vipasyan

Expertise and professionalism for inclusive (mathematics) teaching and learning: reflections on findings from interdisciplinary professionalisation research - Seitz, Simone; Häsel-Weide, Uta; Wilke, Yannik; Wallner, Melina (Teachers and Teaching)

Anchoring and electro-optic switching of liquid crystals on nano-structured surfaces fabricated by two-photon based nano-printing - Zhang, Bingru; Plidschun, Malte; Schmidt, Markus A.; Kitzerow, Heinz-Siegfried (Optical Materials Express)
The alignment of liquid crystals on surfaces plays a central role in optimizing their performances. In this work, a cutting-edge nano-lithography-based method to control the local orientation of a thermotropic liquid crystal is applied to easily available commercial standard materials and evaluated. Parallel nanogrooves on a substrate, created through 3D nanoprinting in a negative-tone photoresin optimized for two-photon polymerization are used for this purpose. Azimuthal anchoring energies of the order from 10 −6 J/m 2 to 10 −5 J/m 2 are found, depending on the spacing, width and depth of the grooves. In part, these values are larger than those reported previously for another photopolymer. Both uniform alignment and spatial patterns of different alignment directions can be realized. Electro-optic studies confirm the suitability of the method for electrically addressable photonic applications and indicate strong polar anchoring.
Keywords: Electronic; Optical and Magnetic Materials

Zusammenarbeit von Frühförderung und Kita im Förderschwerpunkt Sehen - Jesuthasan, Jonitta

Meta-Reinforcement-Learning-Based Current Control of Permanent Magnet Synchronous Motor Drives for a Wide Range of Power Classes - Jakobeit, Darius; Schenke, Maximilian; Wallscheid, Oliver (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

The data awareness framework as part of data literacies in K-12 education - Höper, Lukas; Schulte, Carsten (Information and Learning Sciences)
In today's digital world, data-driven digital artefacts pose challenges for education, as many students lack an understanding of data and feel powerless when interacting with them. This article addresses these challenges and introduces the data awareness framework. It focuses on understanding data-driven technologies and reflecting on the role of data in everyday life. The paper also presents an empirical study on young school students' data awareness. The study involves a teaching unit on data awareness framed by a pretest-posttest design using a questionnaire on students' awareness and understanding of and reflection on data practices of data-driven digital artefacts. The study's findings indicate that the data awareness framework supports students in understanding data practices of data-driven digital artefacts. The findings also suggest that the framework encourages students to reflect on these data practices and think about their daily behaviour. Students learn a model about interactions with data-driven digital artefacts and use it to analyse data-driven applications. This approach appears to enable students to understand these artefacts from everyday life and reflect on these interactions. The work contributes to research on data and AI literacies and suggests a way to support students in developing self-determination and agency during interactions with data-driven digital artefacts.
Keywords: Library and Information Sciences; Computer Science Applications; Education

After-school sports programmes and social inclusion processes in culturally diverse contexts: Results of an international multicase study - Carter-Thuillier, Bastian; López-Pastor, Víctor; Gallardo-Fuentes, Francisco; Carter-Beltran, Juan; Fernández-Balboa, Juan-Miguel; Delgado-Floody, Pedro; Grimminger-Seidensticker, Elke; Sortwell, Andrew (Frontiers in Psychology)
This research aimed to understand the role of after-school sports programs in social inclusion processes in culturally diverse contexts through a multicase study within two locations. The first location was in Spain where immigrant and Spanish students were enrolled, and the other was in Chile with Mapuche-Huilliche students, immigrant and Chilean students. The implemented programs at both sites were similar in their educational focus on socio-educational values, and teaching models (hybridization of teaching games for understanding and cooperative learning) that enhance social inclusion. Using individual and group interviews with teachers, sports coordinators, parents, and students, a qualitative approach was used to identify the factors that facilitate or hinder the social inclusion processes. In addition, the researchers used qualitative observations of the programs over six months using “notes logbook” to record their impressions during the observation process. Results indicated that the implemented sports programs successfully facilitated social inclusion processes, enabling the development of interpersonal skills and relationships between students from different cultural backgrounds. The previous training and experiences of teachers in culturally diverse contexts, and incorporation of traditional sporting games from all cultures, seems to be an important facilitator factor for the inclusion potential of the implemented programs.
Keywords: General Psychology

Zwischen Überwältigung und Beliebigkeit - Wertorientierung im Unterricht als Aufgabe der Lehrpersonenbildung - Schlegel-Matthies, Kirsten (Nachdenken über Lehrerinnen- und Lehrerbildung. Anregungen zur Weiterentwicklung der Pädagogischen Hochschulen in der deutschsprachigen Schweiz. Aus Anlass des 20-Jahre-Jubiläums der Pädagogischen Hochschule Luzern)

Open Research Practices and Cultural Change: A Commentary on “(Why) Are Open Research Practices the Future for the Study of Language Learning?” - Steinhardt, Isabel; Mauermeister, Sylvi; Schmidt, Rebecca (Language Learning)
Keywords: Open Science; Open Science Practices; Cultural Change

The Bot Delusion. ChatGPT and anticipated consequences for research communication - Wieczorek, Oliver; Steinhardt, Isabel; Schneijderberg, Christian; Schmidt, Rebecca; Mauermeister, Sylvi
The reproduction of social inequalities through artificial intelligence (AI) and machine learning via artificial neural networks (ANN) has been demonstrated empirically in various areas of society, for instance in policing and personnel hiring decisions. Yet, a broader discussion is missing to what extent ANN technological developments may affect the scientific enterprise and reinforce or mitigate existing structural inequalities in academia. Focusing on publications and citations as main currencies in science, the anticipated consequences of ChatGPT on the research communication of existing and new knowledges are discussed in three scenarios, which echo the social structures in academia.

Discrete Lagrangian Neural Networks with Automatic Symmetry Discovery - Lishkova, Yana; Scherer, Paul; Ridderbusch, Steffen; Jamnik, Mateja; Liò, Pietro; Ober-Blöbaum, Sina; Offen, Christian (IFAC-PapersOnLine)
By one of the most fundamental principles in physics, a dynamical system will exhibit those motions which extremise an action functional. This leads to the formation of the Euler-Lagrange equations, which serve as a model of how the system will behave in time. If the dynamics exhibit additional symmetries, then the motion fulfils additional conservation laws, such as conservation of energy (time invariance), momentum (translation invariance), or angular momentum (rotational invariance). To learn a system representation, one could learn the discrete Euler-Lagrange equations, or alternatively, learn the discrete Lagrangian function Ld which defines them. Based on ideas from Lie group theory, in this work we introduce a framework to learn a discrete Lagrangian along with its symmetry group from discrete observations of motions and, therefore, identify conserved quantities. The learning process does not restrict the form of the Lagrangian, does not require velocity or momentum observations or predictions and incorporates a cost term which safeguards against unwanted solutions and against potential numerical issues in forward simulations. The learnt discrete quantities are related to their continuous analogues using variational backward error analysis and numerical results demonstrate the improvement such models can have both qualitatively and quantitatively even in the presence of noise.

Memory Gym: Towards Endless Tasks to Benchmark Memory Capabilities of Agents - Pleines, Marco; Pallasch, Matthias; Zimmer, Frank; Preuss, Mike (arXiv:2309.17207)
Memory Gym presents a suite of 2D partially observable environments, namely Mortar Mayhem, Mystery Path, and Searing Spotlights, designed to benchmark memory capabilities in decision-making agents. These environments, originally with finite tasks, are expanded into innovative, endless formats, mirroring the escalating challenges of cumulative memory games such as ``I packed my bag''. This progression in task design shifts the focus from merely assessing sample efficiency to also probing the levels of memory effectiveness in dynamic, prolonged scenarios. To address the gap in available memory-based Deep Reinforcement Learning baselines, we introduce an implementation that integrates Transformer-XL (TrXL) with Proximal Policy Optimization. This approach utilizes TrXL as a form of episodic memory, employing a sliding window technique. Our comparative study between the Gated Recurrent Unit (GRU) and TrXL reveals varied performances across different settings. TrXL, on the finite environments, demonstrates superior sample efficiency in Mystery Path and outperforms in Mortar Mayhem. However, GRU is more efficient on Searing Spotlights. Most notably, in all endless tasks, GRU makes a remarkable resurgence, consistently outperforming TrXL by significant margins. Website and Source Code: https://github.com/MarcoMeter/endless-memory-gym/

Towards active learning: A stopping criterion for the sequential sampling of grain boundary degrees of freedom - Schmalofski, Timo; Kroll, Martin; Dette, Holger; Janisch, Rebecca (arXiv:2302.01603)
Many materials processes and properties depend on the anisotropy of the energy of grain boundaries, i.e.~on the fact that this energy is a function of the five geometric degrees of freedom (DOF) of the interface. To access this parameter space in an efficient way and to discover energy cusps in unexplored regions, a method was recently established, which combines atomistic simulations with statistical methods 10.1002/adts.202100615. This sequential sampling technique is now extended in the spirit of an active learning algorithm by adding a criterion to decide when the sampling has advanced enough to stop. In this instance, two parameters to analyse the sampling results on the fly are introduced: the number of cusps, which correspond to the most interesting and important regions of the energy landscape, and the maximum change of energy between two sequential iterations. Monitoring these two quantities provides valuable insight into how the subspaces are energetically structured. The combination of both parameters provides the necessary information to evaluate the sampling of the 2D subspaces of grain boundary plane inclinations of even non-periodic, low angle grain boundaries. With a reasonable number of data points in the initial design, only a few appropriately chosen sequential iterations already improve the accuracy of the sampling substantially and unknown cusps can be found within a few additional sequential steps.

Assessment of long-term dietary cadmium exposure in children in Germany: Does consideration of data from total diet studies reduce uncertainties from food monitoring programmes? - Kolbaum, AE; Jung, C; Jaeger, A; Libuda, Lars; Lindtner, O (Food Chem Toxicol)

The Broken Leg of Algorithm Appreciation: An Experimental Study on the Effect of Unobserved Variables on Advice Utilization - Leffrang, Dirk (Wirtschaftsinformatik Conference)
Despite the widespread use of machine learning algorithms, their effectiveness is limited by a phenomenon known as algorithm aversion. Recent research concluded that unobserved variables can cause algorithm aversion. However, the impact of an unobserved variable on algorithm aversion remains unclear. Previous studies focused on situations where humans had more variables available than algorithms. We extend this research by conducting an online experiment with 94 participants, systematically varying the number of observable variables to the advisor and the advisor type. Surprisingly, our results did not confirm that an unobserved variable had a negative effect on advice-taking. Instead, we found a positive impact in an algorithm appreciation scenario. This study provides new insights into the paradoxical behavior in which people weigh advice more despite having fewer variables, as they correct for the advisor's errors. Practitioners should consider this behavior when designing algorithms and account for user correction behavior.
Keywords: Algorithm aversion; Data; Decision-making; Advice-taking; Human-Computer Interaction

Early Depression Detection with Transformer Models: Analyzing the Relationship between Linguistic and Psychology-Based Features - Halimeh, Haya; Caron, Matthew; Müller, Oliver (Hawaii International Conference on System Sciences)
Clinical depression is a serious mental disorder that poses challenges for both personal and public health. Millions of people struggle with depression each year, but for many, the disorder goes undiagnosed or untreated. Over the last decade, early depression detection on social media emerged as an interdisciplinary research field. However, there is still a gap in detecting hesitant, depression-susceptible individuals with minimal direct depressive signals at an early stage. We, therefore, take up this open point and leverage posts from Reddit to fill the addressed gap. Our results demonstrate the potential of contemporary Transformer architectures in yielding promising predictive capabilities for mental health research. Furthermore, we investigate the model’s interpretability using a surrogate and a topic modeling approach. Based on our findings, we consider this work as a further step towards developing a better understanding of mental eHealth and hope that our results can support the development of future technologies.
Keywords: Social Media and Healthcare Technology; early depression detection; liwc; mental health; transfer learning; transformer architectures

Analyzing the Needs of Ukrainian Refugees on Telegram in Real-Time: A Machine Learning Approach - Reimann, Raphael; Caron, Matthew (Wirtschaftsinformatik)
The humanitarian crisis resulting from the Russian invasion of Ukraine has led to millions of displaced individuals across Europe. Addressing the evolving needs of these refugees is crucial for hosting countries and humanitarian organizations. This study leverages social media analytics to supplement traditional surveys, providing real-time insights into refugee needs by analyzing over two million messages from Telegram, a vital platform for Ukrainian refugees in Germany. We employ Natural Language Processing techniques, including language identification, sentiment analysis, and topic modeling, to identify well-defined topic clusters such as housing, financial and legal assistance, language courses, job market access, and medical needs. Our findings also reveal changes in topic occurrence and nature over time. To support practitioners, we introduce an interactive web-based dashboard for continuous analysis of refugee needs.

TemporalFC: A Temporal Fact Checking Approach over Knowledge Graphs - Qudus, Umair; Röder, Michael; Kirrane, Sabrina; Ngomo, Axel-Cyrille Ngonga (The Semantic Web – ISWC 2023)
Verifying assertions is an essential part of creating and maintaining knowledge graphs. Most often, this task cannot be carried out manually due to the sheer size of modern knowledge graphs. Hence, automatic fact-checking approaches have been proposed over the last decade. These approaches aim to compute automatically whether a given assertion is correct or incorrect. However, most fact-checking approaches are binary classifiers that fail to consider the volatility of some assertions, i.e., the fact that such assertions are only valid at certain times or for specific time intervals. Moreover, the few approaches able to predict when an assertion was valid (i.e., time-point prediction approaches) rely on manual feature engineering. This paper presents TEMPORALFC, a temporal fact-checking approach that uses multiple sources of background knowledge to assess the veracity and temporal validity of a given assertion. We evaluate TEMPORALFC on two datasets and compare it to the state of the art in fact-checking and time-point prediction. Our results suggest that TEMPORALFC outperforms the state of the art on the fact-checking task by 0.13 to 0.15 in terms of Area Under the Receiver Operating Characteristic curve and on the time-point prediction task by 0.25 to 0.27 in terms of Mean Reciprocal Rank. Our code is open-source and can be found at https://github.com/dice-group/TemporalFC.
Keywords: temporal fact checking · ensemble learning · transfer learning · time-point prediction · temporal knowledge graphs

Facial Recognition in Law Enforcement - Hälterlein, Jens (The Oxford Handbook of the Sociology of Machine Learning)
Abstract This chapter discusses the use of facial recognition technology (FRT) by law enforcement with a special focus on machine learning applications. First, FRT is situated in the larger context of the rise of video surveillance and a shift in Western security culture. The chapter shows how the promise of FRT addresses the problems of video surveillance. Then, it explains how FRT works and how machine learning techniques such as eigenface and convolutional neural networks come into play. Afterward, it explains how the accuracy and effectiveness of FRT are evaluated and why it is important to take the interplay of human operators and FRT systems into account. Finally, several controversies around the police use of FRT are presented and the limits of technological solutions to the problem of bias are demonstrated.

Neue Sorgfaltspflichten für Unternehmen des Agrar- und Ernährungssektors: Empfehlungen zu aktuellen Gesetzesentwicklungen - Spiller, Achim; Nieberg, Hiltrud; Renner, Britta; Balmann, Alfons; Birna, Regina; Bosy-Westphal, Anja; Buyken, Anette; Döring, Thomas; Feindt, Peter; Götz, Kai-Uwe; Linseisen, Jakob; Nöthlings, Ute; et al.
Zitieren als: Wissenschaftlicher Beirat für Agrarpolitik, Ernährung und gesundheitlichen Verbraucher- schutz beim BMEL (2023): Neue Sorgfaltspflichten für Unternehmen des Agrar- und Ernährungssektors: Empfehlungen zu aktuellen Gesetzesentwicklungen. Gutachten. Berlin.

Phasenübergreifende Zusammenarbeit in der digitalisierungsbezogenen Lehrer*innenbildung gestalten - Drossel, Kerstin; Rothstein, Björn (Themenheft im Online-Journal ‚Herausforderung Lehrer_innenbildung – Zeitschrift zur Konzeption, Gestaltung und Diskussion (HLZ)‘)
Der Beitrag diskutiert am Beispiel der Linguistik Möglichkeiten und Grenzen der phasenübergreifenden Zusammenarbeit in der digitalisierungsbezogenen Lehrer*innenbildung und verdeutlicht daran das Anliegen und die Systematik des Themenheftes. Zahlreiche Studien belegen die Ausbaufähigkeit der digitalisierungsbezogenen Lehrer*innenbildung hinsichtlich der Nutzung digitaler Medien für die Gestaltung schulischer Lehr- und Lernprozesse und geben Anlass zur Weiterentwicklung mit dem Ziel, einen kumulativen Kompetenzaufbau und die Zusammenarbeit der Phasen der Lehrer*innenbildung zu fördern. Als besondere Formen einer solchen Zusammenarbeit werden in diesem Themenheft „Communities of Practice“, „Service Learning“ und das Praxissemester in Nordrhein-Westfalen (NRW) aufgegriffen. Während die phasenübergreifende Zusammenarbeit in „Communities of Practice“ durch wechselseitige Impulse den Aspekt der Multiperspektivität fokussiert, verbindet „Service Learning“ auf der Basis ko-konstruktiver Zusammenarbeit das Erproben und Reflektieren erworbenen Wissens durch soziales Engagement im schulischen Umfeld. Das NRW-Praxissemester gilt als institutionalisierte Schnittstelle der gemeinsamen Lehrer*innenbildung in Form einer verpflichtenden institutionalisierten Kooperation. Sowohl theoretisch-konzeptionelle als auch empirische Beiträge zu den genannten Formen phasenübergreifender Zusammenarbeit in der digitalisierungsbezogenen Lehrer*innenbildung sollen das Verständnis an dieser Stelle vertiefen.

Fostering students’ resilience. Analyses towards factors of individual resilience in the computer and information literacy domain - Drossel, Kerstin; Eickelmann, Birgit; Vennemann, M.; Fröhlich, Nadine (Towards a collaborative society through creative learning)